Tingkat Kesadaran Hukum Masyarakat dalam Membayar Pajak Bumi dan Bangunan Perkotaan di Kelurahan Lasiana Kota Kupang - Liliany Tefa; Hernimus Ratu Udju; Cyrilius W. Taran Lamataro (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Land and Building Tax (PBB) is a tax on land and buildings. Earth is the surface of the earth and the body of the earth underneath, including land and waters, as well as the sea in the territory of the Republic of Indonesia. Building is a technical construction that is planted or permanently attached to land and water for residence, place of business, and place of business. This research is an empirical legal research conducted in the Government of East Nusa Tenggara Province, namely in Lasiana Village, and the Regional Revenue Office (Dispenda) of Kupang City, related to the topics discussed in this paper. The data is analyzed descriptively-qualitatively. Based on the results the authors show that There is still a lack of public awareness in paying taxes. Taxpayers view prioritizing basic needs that must be met and prioritized. And view the tax as an extortionist so that many taxpayers complain that the increase in the tax burden is the same as the increase in their burden. In encouraging taxpayers to pay Land and Building Tax because of the inhibiting factors of low public awareness in paying Land and Building Tax.